TIN EXPLOITATION: AN ECOCRITICISM APPROACH IN ANDREA HIRATA’S RAINBOW TROOPS - Supian Supian; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2022)
This research was aimed at reflecting how Hirata reveals the tin exploitation in Belitung Island through his debut novel, Laskar Pelangi. It is significant and worthy research as it is an effort to raise awareness and understanding of human beings about the importance of nature and the environment, especially awareness for people who have the power to determine nature protection policies and the importance of nature conservation for the preservation of ecosystems for future generations. This research applied the theory of ecocriticism proposed by Gerrard supported by the theory offered by Gutti, Aji and Magaji. This research uses descriptive qualitative in which the data obtained from the novel are analyzed to reveal the process of tin exploitation in Belitung Island. The research results show that tin exploitation in Belitung Island is carried out both in traditional and modern ways. Traditional tools used to mine tin are phok, aichang, khaknai and kiaw to make water embankments and shovels to dig soil, while modern tools used to mine tin are machines in the forms of heavy equipment, such as dredgers and excavators. Traditional tin mining activities in Belitung which are carried out without a Mining Business Permit or Unlicensed Mining is also revealed in the novel.